Import substitution of production automation ("Journal "U". Economy. Management. Finance.", 2022)
This article considers the problem of Russian import substitution of production automatics. The positive aspects of import substitution and the advantages of domestic production are described. The works of scientists who have studied this issue are also given. The successes of Russian industrial and technological production are mentioned. Examples are given of plants that are currently on course to develop and produce the necessary equipment. Also a brief analysis of the implemented directions of import substitution in the field of automated control systems by Russian developments.
Keywords: economy; import substitution; industrial automation; fire automation; market; problem; sanctions, complex; engineering systems; production